Real-world experience of angiotensin receptor-neprilysin inhibitors in patients with heart failure and dialysis - Yang, I-Ning; Huang, Chi-Ya; Yang, Chun-Ting; Toh, Han-Siong; Chang, Wei-Ting; Su, Li-Wei; Lin, Yu-Min; Wang, Ming-Cheng; Wang, Hsien-Yi; Liao, Chia-Te (Frontiers in Cardiovascular Medicine, 2024)
Introduction Although angiotensin receptor-neprilysin inhibitor (ARNI) has shown promise in patients with heart failure and reduced ejection fraction (HFrEF), the treatment effect in HFrEF patients with end-stage renal disease (ESRD) undergoing dialysis is uncertain. This study aimed to examine the real-world effects of ARNI vs. angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEI/ARB) in this subpopulation. Methods This multi-institutional, retrospective study identified 349 HFrEF patients with ESRD on dialysis, who initiated either ARNI or ACEI/ARB therapy. Efficacy outcomes included rates of hospitalization for heart failure (HHF) and mortality, as well as changes in echocardiographic parameters. Safety outcomes encompassed hypotension and hyperkalemia. Treatment effects were assessed using Cox proportional hazards models, with additional sensitivity analyses for robustness. Results Out of 349 patients screened, 89 were included in the final analysis (42 in the ARNI group and 47 in the ACEI/ARB group). After 1 year of treatment, echocardiographic measures between the two groups were comparable. The primary composite rate of HHF or mortality was 20.6 events per 100 patient-years in the ARNI group and 26.1 in the ACEI/ARB group; the adjusted hazard ratio was 0.98 (95% CI: 0.28–3.43, P = 0.97). Their safety outcomes did not differ significantly. Sensitivity analyses, including repetitive sampling, propensity score matching, and extended follow-up, corroborated these findings. Conclusion ARNI has proven effective in treating HFrEF patients; however, significant benefits were not observed in these patients with ESRD undergoing dialysis compared with ACEI/ARB in this real-world cohort. Future research employing a more extended follow-up period, larger sample size, or randomized design is warranted to investigate the treatment effects in this subpopulation.